Innovation districts as strategic urban projects: the emergence of strategic spatial planning for urban innovation - Kalliomäki, Helka (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2025)
This paper contributes to the emerging research on innovation districts (IDs) by conceptualizing them as strategic urban projects. IDs connect innovative activities to their spatial foundations and thus provide a territorial framework for strategic spatial planning efforts. The extant literature on IDs, focusing mainly on ID characteristics and placemaking, has failed to acknowledge that ID development requires an integrated planning approach to realize the so-called new union between form and function, which is often executed via strategic urban projects. Integrated planning, as discussed in the literature on strategic spatial planning, emphasizes coordination both between a range of stakeholder interests and between administrative sectors and spatial scales. This, in turn, is often rooted in path-dependent connections between diverse sectors and organizations. A case study examines the gradual adoption of the new strategic planning approach while the Turku Science Park area in the city of Turku, Finland, was being transformed into an ID. It demonstrates the rise of a new integrated rationale in contemporary urban planning and economic development, one that strategically envisions a spatial form for economic development objectives. The case offers lessons for academic and policy debates on ID development, underscoring competence building in strategic spatial planning.